Total Synthesis of Camptothecins: An Update - Chen, Lei; Chen, Fen-Er (Synlett, 2017)
Over the last few decades, considerable research efforts have been directed toward the development of effective chemical syntheses of camptothecin and its analogs. The last comprehensive review of this area was published in 2003 and many effective new methods have since been reported for the stereoselective synthesis of the camptothecin alkaloids. In this account, we have summarized most of the novel synthetic approaches developed for the synthesis of camptothecins during the last decade. We have focused on strategies for the construction of the pentacyclic ring system and the different methods used to install the chiral quaternary center on the E ring of camptothecin.1 Introduction2 Synthesis of Racemic Camptothecins3 Enantioselective Synthesis of Camptothecins3.1 Sharpless Asymmetric Dihydroxylation3.2 Catalytic Asymmetric Cyanosilylation3.3 Auxiliary-Induced Asymmetric Carbonyl Addition3.4 Catalytic Asymmetric Ethylation3.5 Asymmetric Hydroxylation4 Conclusion
Keywords: camptothecin; total synthesis; asymmetric synthesis; alkaloids; antitumor activity